The Influence of Sharia Capital and Financial Literacy on Business Income: Survey of Wafa Al Fitrah Micro Wakaf Bank Customers - AFIFAH FITRIANA; LILIK RAHMAWATI (UIN Mataram, 2023)
This research uses quantitative methods. The population used is the Wafa Al Fitrah Micro WaqfBank customers, totaling 80 people. The sampling technique used is a saturated sample orsaturation sample, which uses the entire population. Data collection techniques used are usingquestionnaires and interviews. Data processing and analysis techniques in this study used theclassical assumption test, multiple regression analysis and hypothesis testing. The results of thisstudy indicate that simultaneously capital and Islamic financial literacy affect operating incomewith an F-count of 14.296 > F-table of 3.0178, with a significant value of 0.000. As for partially,capital has a positive effect on business income with a t-count value of 3.091 > t-table of 1.990with a significant value of 0.003. Islamic financial literacy has no effect on income with a t-countvalue of 1.859 > t-table of 1.990 with a significant value of 0.67. It can be concluded thatsimultaneously capital and Islamic financial literacy have a significant effect on the operatingincome of Wafa Al-Fitrah Micro Waqf Bank customers, while partially capital has a significanteffect on operating income and Islamic financial literacy has no significant effect on Wafa Al-Fitrah Micro Waqf Bank operating income.